Changes in the Levels of Abscisic Acid and Its Metabolites in Excised Leaf Blades of Xanthium strumarium during and after Water Stress - Zeevaart, Jan A. D. (1980)
The time course of abscisic acid (ABA) accumulation during water stress and of degradation following rehydration was investigated by analyzing the levels of ABA and its metabolites phaseic acid (PA) and alkalihydrolyzable conjugated ABA in excised leaf blades of Xanthium strumarium. Initial purification was by reverse-phase, preparative, high performance liquid chromatography (HPLC) which did not require prior partitioning. ABA and PA were purified further by analytical HPLC with a μBondapak-NH(2) column, and quantified by GLC with an electron capture detector. The ABA content of stressed leaves increased for 4 to 5 hours and then leveled off due to a balance between synthesis and degradation. Since PA accumulated at a constant rate throughout the wilting period, it was concluded that the rate of ABA synthesis decreased after the first 4 to 5 hours stress. Conjugated ABA increased at a low rate during stress. This is interpreted to indicate that free ABA was converted to the conjugated form, rather than the reverse. Following rehydration of wilted leaves, the ABA level immediately ceased increasing; it remained constant for 1 hour and then declined rapidly to the prestress level over a 2- to 3-hour period with a concomitant rise in the PA level. In contrast to the rapid disappearance of ABA after relief of stress, the high PA content of rehydrated leaves declined only slowly. The level of conjugated ABA did not change following rehydration, indicating that conjugation of ABA was irreversible. Detached Xanthium leaves that were subjected to a wilting-recovery-rewilting cycle in darkness, responded to the second wilting period by formation of the same amount of ABA as accumulated after the first stress period.